Diel Vertical Migration of Zooplankton in Lakes and Oceans causal explanations and adaptive significances - Ringelberg, Joop (Springer Netherlands : Imprint: Springer, 2010)
The book deals with Diel Vertical Migration (DVM) of zooplankton in oceans and lakes and is the first critical discussion of the literature in 100 years of research. The accent is on photo-response experiments that revealed the physiological fundament unifying migration behaviour in both biotopes. Accelerations in relative changes in light intensity of dawn and dusk are the stimuli that trigger a PhotoBehaviour Mechanisms (PBM) evolved to realise predator evasion and starvation prevention. Physiology and behaviour are tuned to these adaptive goals. A "set of ecological factors" is necessary and an algorithm shows the operation of the "set". However, not only the kinetic component of behaviour is based on light, also orientation but now the angular light distribution is responsible. Contrast orientation as in Daphnia may also hold for other animals, for example, Euphausia.The application of the PBM in lakes and oceans is demonstrated amongst other for the vertical movements of Sound Scattering Layers. These layers move faster, slower or as fast as an isolume which was a problem for the decennia long explanation that migrating animals followed an optimal light intensity. The enigma was solved. Using time series of changes in population size, egg ratios, development times and death rates due to predation by juvenile fish, the influence of DVM on population dynamics was analysed. Finally, covering the flow of matter in the traditional food web by a network of information transitions illustrates the controlling function of infochemicals, such as fish kairomones.